Cracking the Code: An effectiveness study - Kelly, Chrissy Ann (Curtin University, 2016)
This study employed a pre-test post-test group design to evaluate the effectiveness of the Cracking the Code (CtC) Program with students aged 3;8–5;4. CtC is a teacher implemented classroom based program, designed to target phonological awareness (PA) and alphabet knowledge. Results showed that children in the experimental condition improved significantly more in PA, alphabet knowledge, non-word reading and non-word spelling after the intervention than the control group, thus demonstrating the effectiveness of CtC.